Situasi dan Proyeksi Kuantitas Penduduk Kota Tasikmalaya Tahun 2045 - Arip Nugraha, Junjun (LPPM IAIT, 2024)
The research is intended to provide a scientific description as supporting research for the preparation of the Grand Design Document for Population Development of Tasikmalaya City, by presenting an overview of the situation and projected population quantity for Tasikmalaya City in 2045. This research uses an exploratory sequential design approach. The population of Tasikmalaya City at the Golden Indonesia moment in 2045 is estimated to reach 891,049 people with growth of 2.82% from 2040. The sex ratio continues to decline to below 100. The Total Fertility Ratio in 2022 is 2.19 (towards a stable population), while the Age Specific Fertility Rate in 2022 reaches 12.80 which is in line with the 2020–2024 RPJMN target. In 2023, the city of Tasikmalaya is projected to start entering an aging population. The demographic bonus is at the ongoing demographic transition stage. Crude Birth Rate is 16.91, including the low category. The median age at first marriage reached 20.51, which is not in line with the 2020–2024 RPJMN target. The rate of use of modern contraception has reached 62.81 in accordance with the 2020–2024 RPJMN target. The prevalence of using long-term contraceptive methods has reached 29.21, which is in line with the 2024 BKKBN target. The decrease in unmet need is a positive thing.